DESIGN OF TEACHING MATERIAL DEVELOPMENT FOR LEARNING METHODOLOGY IN DEPARTEMENT OF ISLAMIC ELEMENTARY SCHOOL TEACHER EDUCATION OF UIN RADEN FATAH PALEMBANG - Tutut Handayani; Mardiah Astuti; Hani Atus Sholikhah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The aim of this research is designing learning methodology teaching materials and testing the feasibility of teaching materials of learning methodology based on validity, practicality, and effectiveness tests. The research methodology used was Research and Development (RnD). Research data collection included observation, questionnaires, and interviews. The model development instruments were expert review, one two one, and small group. The subjects of this research were students of the fifth semester of PGMI FITK UIN Raden Fatah Palembang Study Program. The results show that the findings with validity test is very valid, it is 86%,practicality test with the result is very practical 84%, and effectiveness test with the result is very effective with the result85%.